ダイ 1 ジ ナンキョク チイキ カンソクタイ キショウ ブモン ホウコク - 守田, 康太郎; モリタ, ヤスタロウ; 清野, 善兵衛; セイノ, ゼンベイ; 安井, 正; ヤスイ, マサシ; 久我, 雄四郎; クガ, ユウシロウ; 田島, 成昌; タジマ, ナリマサ; 村越, 望; ムラコシ, ノゾミ; et al. (国立極地研究所, 1958)
P(論文) departmental bulletin paper